EFFECT OF CLIMATE ON LITTER TRAITS OF CROSSBRED PIGS IN MIZORAM (Indian Journal of Animal Production and Management, 2015)
A study on seasonal effect of climate on the litter traits of cross bred pigs was undertaken in different districts of Mizoram such as Aizawl, Lunglei, Champhai and Kolasib. Data of 11 years i.e. January 2002 to December 2012 was collected from a total of 11,376 animals. Meteorological data was also collected from MIRSAC. The average litter size at birth Lalremruata et al. ranges from 6.469±0.15 to 6.853±0.15 and litter weight from 7.100±0.20 to 7.843±0.19 kg. However, there was non-significant difference between litter traits at the time of piglet birth in different seasons. However, at the time of weaning, average litter size ranges from 5.484±0.14 to 5.995±0.14 and litter weight ranges from 49.92±1.28 to 55.27±1.20 kg. There was significant differences in litter size at weaning (P
Keywords: Season; litter traits; performance; cross-bred pigs